Exploration of Bioactive Compounds, Antioxidant and Antibacterial Properties, and Their Potential Efficacy Against HT29 Cell Lines in Dictyota bartayresiana - Durairaj Swarna Bharathi; Andiyappan Boopathy Raja; Suganthi Nachimuthu; S. Thangavel; Karthik Kannan; Sengottaiyan Shanmugan; Vinaya Tari (Marine Drugs, 2025)
This study investigates the rare seaweed alga Dictyota bartayresiana lamour for biological activity. Antioxidant and antibacterial activities were examined. An MTT assay was carried out to examine cytotoxicity activity against colon cancer cells. The HPTLC analysis was performed for four different extracts, which exhibited clear flavonoid band formation at 254 nm and 366 nm with varied ranges of Rf values: methanolic extract (Rf 0.87), acetone extract (Rf 0.82), and benzene (Rf 0.83). Methanolic Extract Fraction One (MEF1) has a distinct band formation at 366 nm, it is shown to have the highest inhibition (6.20 ± 0.53 mm) against Escherichia coli, and the MTT assay reveals that the aqueous extract of Dictyota bartayresiana extract has an IC50 value of 300 µg/mL. It is divulged that methanolic extract shows the highest phytochemical compound level among the four extracts of Dictyota bartayresiana. A GC/MS analysis was employed to investigate the flavonoid profile of the crude seaweed extract. Although LC/MS is typically preferred for flavonoid analysis due to thermal sensitivity, GC/MS was used in this study owing to time constraints, with optimized conditions to reduce thermal degradation. The GC-MS analysis identified Quinoline and other flavonoids, suggesting potential bioactivity. The cytotoxicity activity of MEF1 shows that the development of a promising drug may be evaluated from a seaweed source. The present study provides excellent insight with the first report of the biologically active compound of Dictyota bartayresiana.